Cultural Diplomacy of The Mahabharata: A Case Study of its Application with Special Reference to Modern India - Mishra, Deepanjali (Prabandhan: Indian Journal of Management, 2019)
.India's tradition of diplomacy of implementing extroversive interests dates back to ancient times, leading towards the concept of strategic culture, and the well - known Hindu epics like Ramayana and Mahabharata could be the greatest exemplars of the institution of diplomacy. In Mahabharata, Lord Krishna had gone to Hastinapur as a peace envoy on a diplomatic mission to have a talk with Duryodhan and played the role of a mediator to avoid war between the Pandavas and the Kauravas. The war was termed as Dharmayuddha, which means the war of righteousness. It was fought with well-defined norms with highly efficient diplomatic contact between the two warring sides. The concepts of immunity and amnesty were well-established and were respected. A diplomat needed to be treated with dignity and respect. In today's world, an ambassador is a diplomat who pursues the interests of his/her own country with other countries by implementing the policies of the state and adopts different techniques of strengthening the public relations and he/she participates in high level social gatherings and attends public functions. The role of international relations has undergone a remarkable change in the context of changing power environments, nuclear policies, technological revolutions, and the world faces many more challenges regarding international security, disarmament, terrorism, global warming, etc. The present study discussed how Prime Minister Narendra Modi is establishing cultural diplomacy as a strategic decision maker to firmly establish India's position in South Asia and the world at large.